1998
DOI: 10.1108/01445159810239765
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional simulation of accommodation

Abstract: Limited precision of manufactured parts and limited repeatability of industrial robots are the two main sources of uncertainty in the automated assembly environment. Different accommodation techniques are used to improve the reliability of the assembly process. Simplified representation of the accommodation task environment, especially for precision assembly tasks, however, does not allow a reliable assessment of the possibilities for successful assembly. Presents a method for 3D simulation of the accommodatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…RCC wrists, different control strategies etc.). 7,8 Setchi et al 9 have suggested a 3D simulation programme for the peg-in-hole insertion process. This approach considers the insertion process as a sequence of discrete events, and models the process as a transition from one contact situation to another.…”
Section: Introductionmentioning
confidence: 99%
“…RCC wrists, different control strategies etc.). 7,8 Setchi et al 9 have suggested a 3D simulation programme for the peg-in-hole insertion process. This approach considers the insertion process as a sequence of discrete events, and models the process as a transition from one contact situation to another.…”
Section: Introductionmentioning
confidence: 99%